Evolution, cognition, and the history of religion : a new synthesis : festschrift in honour of Armin W. Geertz - Geertz, Armin W., 1948-; Petersen, Anders Klostergaard (Supplements to Method & Theory in the Study of Religion, 2019)
Evolution, Cognition, and the History of Religion: A New Synthesis comprises 41 chapters that push for a new way of conducting the study of religion, thereby, transforming the discipline into a genuine science of religion. The recent resurgence of evolutionary approaches on culture and the increasing acknowledgement in the natural and social sciences of culture's and religion's evolutionary importance calls for a novel epistemological and theoretical framework for studying these two areas. The chapters explore how a new scholarly synthesis, founded on the triadic space constituted by evolution, cognition, cultural and ecological environment, may develop. Different perspectives and themes relating to this overarching topic are taken up with a main focus on either evolution, cognition, and/or the history of religion.